Extreme Price Risk on the Market of Soybean Meal - Just, Małgorzata; Śmiglak-Krajewska, Magdalena (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
The price of soybean meal in Poland is related with the price quoted on the Chicago Board of Trade (CBOT). The aim of this study was to assess and compare extreme price risk on the market of soybean meal in Poland and on the market of futures contracts for soybean meal and soybean, quoted on the CBOT. For this purpose analyses were conducted on daily price series for soybean meal ex quay port of destination Gdynia as well as historical time series for daily closing quotes for futures contracts for soybean meal and soybean at the CBOT, from 23 February 2012 to 8 July 2015. Extreme risk was assessed using two measures: value at risk and expected shortfall, applying the extreme value theory. Results of analyses indicate a higher level of extreme price risk on the market of futures contracts for soybean meal and soybean. For both contracts we observe an asymmetry of the risk profile for the long and short positions in these contracts. No marked asymmetry in the risk profile was observed on the market of soybean meal in Poland.